How Ireland Voted 2002 - Gallagher, Michael. author. aut Link
XXXV, 276 p.
Keywords: How Ireland Voted 2002 provides an in-depth analysis of the Irish general election. Continuing an established series of election studies, it sets out the context of the campaign, assesses the impact of the political parties' marketing strategies, and presents first-hand candidate campaign diaries. It analyzes voting patterns employing both aggregate data and survey evidence, discusses the post-election negotiations leading to the formation of the new government, and considers the implications for the future of the Irish party system.